Core temperature and fatigue - Marshall, N. (Cycle coaching, 2000)
Our new knowledge also puts current pre-event warm-up practice in a rather different light, at least in warm-to-hot weather conditions. A long, intense warm-up for a short event will impose its own thermal stress, so that central fatigue during the event itself will occur earlier - just as taking a hot bath prior to the race would bring forward the point at which the critical core temperature is approached. I suggest that the objective of the warm-up should be to protect muscles and joints from injury, and match metabolic rate to the anticipated demands of the event, while increasing core temperature to the smallest extent compatible with those objectives. As an example, before a10ml time trial on a warm day I currently recommend that athletes prepare their joints and muscles for the demands of the race effort by pedalling a low gear for about 10 minutes. In the last five minutes of the warm-up, I have them do three or four 30-second intervals at race pace in an attempt to 'warn' their muscle metabolism of what is about to be demanded of it; they then go from warm-up to start line with the smallest practicable delay. Truly optimal warmup strategies for each event and set of conditions remain to be evolved. As coaches, we strive to ensure that our athletes are well prepared by their training and diet, that they adopt effective nutritional strategies during events, that their tactics or pacing strategy are well founded... If we fail to take heat stress and its role in central fatigue into consideration, we may be missing out on giving our athletes an important competitive edge.